The socio-politics of (Re)constructing home in a post-displacement context in rural Zimbabwe - Elmon Mudefi; Wilson Akpan; Alice Stella Kwizera (Social Sciences and Humanities Open)
This paper contributes to and advances the sociological discourse on ‘homing’ by examining the implications of the socio-political dynamics of resettlement, with particular reference to the 2014 Tokwe-Mukorsi flood victims in rural Zimbabwe, five years after they were resettled in Chingwizi. The article highlights the intricacies encountered by displaced persons as they strive to establish what they consider an ideal home – one that guarantees, at the very least, food security, shelter, safety, property rights, identity, and a sense of belonging. Drawing on actor-network theory, the article utilizes empirical qualitative data gathered using interviews and focus groups from displaced persons and government officials. The intention was to illuminate how homing experiences are influenced by socio-ecological encounters between displaced persons and other key actors. From the adversities resulting from the floods, the victims waded not in a socio-ecological vacuum or neutral space but in a hotly contested terrain as they sought to adapt to climatic conditions at the new location, overcome past cultural fixations, and ultimately build a new homely life. The study found that these processes, inter alia, meant navigating the complex socio-political dynamics of exclusion and marginalization that rendered the quest for an ideal home untenable.